The recovery rate of embryos using eight different protocols of synchronization and superovulation in sheep - Caroline, WieWie; Summers, P.M (Indonesian Animal Sciences Society, 1999)
A large number of embryo recovery and also transferable is a major problem in superovulation regime of the ewe. The purpose of the study was to recover a large number of transferable embryos by using eight different protocols of synchronization and superovulation for each group of sheep. In this study, the Merino ewes aged between 1-3 years and rams between 2-5 years were used. The embryos were collected surgically on day-7, day-8, day-9 and day-10 after the onset of oestrus. The mean number of normal embryos recovered (3.90Â±1.49) at day 7 with oFSH alone (4-4.5ml) and the combination of oFSH (4-4.5ml) with PMSG (400 IU) was significantly higher (P<0.01) than in the sheep treated with PMSG (1,200 IU) alone (0.92Â±0.32). The results of this study showed that a mixture of oFSH and PMSG gives the best result in embryo recovery of the ewe and also transferable compared to other methods. Â Key words : Embryo, sheep, superovulation